DETECTION OF GOING CONCERN AUDIT OPINION BASED ON DISCLOSURE, FINANCIAL CONDITION AND OPINION SHOPPING - Fika Trya Ramadhani; Wiwit Apit Sulistyowati (Universitas Pamulang, 2020)
Going concern shows assumptions in the financial reporting of an entity relating to the viability of an undertaking. Therefore, the role manager is critical to realize its business continuity. This research aims to analyze the influence of disclosure, financial condition, and opinion shopping on the acceptance of audit opinions going concern on manufacturing companies of various industries listed on the Indonesia Stock exchange for a period of years 2014 – 2016. This article uses the verificative method and the sample selection using the purposive sampling method. Sample selection results obtained 90 company data. This study used the analysis of logistic regression, and the results showed that the opinion shopping influence on the acceptance of the audit opinion of going concern while the disclosure and financial condition does not affect the acceptance of the audit opinion Going concern.